Lightweight Deep Learning Architectures for Ophthalmic Disease Detection: MobileNet Variants Applied to Glaucoma Classification - Baydogan, Cem (Fevzullah TEMURTAŞ, 2025)
Glaucoma is a critical ophthalmological disease affecting millions of people worldwide, leading to irreversible optic nerve damage and permanent vision loss if diagnosed late. The disease often presents with no obvious clinical findings in its early stages, coupled with a high reliance on expert judgment, leading to time-consuming and misclassification risks in current diagnostic processes. This makes the integration of artificial intelligence (AI)-based automated systems into clinical decision support processes a crucial requirement for early and accurate glaucoma detection. This study proposes a hybrid approach based on the integrated use of lightweight deep learning (DL) architectures and machine learning (ML)-based classifiers for the automatic classification of glaucoma from fundus images. The proposed hybrid architecture utilizes MobileNetv1, MobileNetv2, and MobileNetv3 (small and large) architectures as the core components of the model. The MobileNet family was chosen due to its low parameter count, high computational efficiency, suitability for real-time operation in mobile and embedded systems, and its ability to effectively extract meaningful deep features from fundus images. Furthermore, in this study, high-dimensional deep feature vectors were extracted from fundus images using these pre-trained models. These features were then processed with different ML classifiers, such as Extreme Gradient Boosting (XGBoost), Support Vector Machine (SVM), Lightweight Gradient Boosting Machine (LGBM), Categorical Gradient Boosting (CatBoost), and k-Nearest Neighbor (kNN), creating a comprehensive hybrid classification framework that combines the strengths of both DL and traditional ML methods. Classification metrics such as accuracy, precision, recall, F-score, and area under curve (AUC) were used for performance evaluation. Experimental findings indicate that the MobileNetv2+SVM hybrid model, in particular, exhibits significant superiority. This hybrid model achieved the highest performance levels in the study, with 0.9409 accuracy, 0.9229 recall, 0.9221 F-score, and 0.9229 AUC. However, the highest precision value (0.9264) was obtained with the MobileNetv3(small)+LGBM hybrid model, demonstrating that different MobileNet variants can provide strong discrimination performance when effectively integrated with various classifiers. The results demonstrate that MobileNet-based deep feature extraction offers high discrimination in glaucoma classification and that the proposed hybrid approach is a reliable, fast, and computationally efficient solution suitable for use in clinical decision support systems. This study provides an important foundation for the development of low-cost and real-time early glaucoma detection systems.

Glokom, dünya genelinde milyonlarca insanı etkileyen ve geç fark edildiğinde geri dönüşü olmayan optik sinir hasarı ve kalıcı görme kaybına yol açan kritik bir oftalmolojik hastalıktır. Hastalığın erken evrelerinde genellikle belirgin bir klinik bulgu ile ortaya çıkmaması, uzman değerlendirmelerine olan yüksek bağımlılık, mevcut tanı süreçlerinde zaman kaybına ve yanlış sınıflandırma riskine neden olabilmektedir. Bu durum, glokomun erken ve doğru tespiti için yapay zekâ (AI) tabanlı otomatik sistemlerin klinik karar destek süreçlerine entegrasyonunu önemli bir gereklilik hâline getirmektedir. Bu çalışmada, glokomun fundus görüntülerinden otomatik olarak sınıflandırılmasına yönelik hafif derin öğrenme (DL) mimarileri ve makine öğrenmesi (ML) tabanlı sınıflandırıcıların bütünleşik kullanımına dayanan hibrit bir yaklaşım önerilmektedir. Önerilen hibrit yapıda, modelin temel bileşeni olarak MobileNetv1, MobileNetv2 ve MobileNetv3 (small ve large) mimarilerinden yararlanılmıştır. MobileNet ailesinin tercih edilme nedeni; düşük parametre sayısı, yüksek hesaplama verimliliği, mobil ve gömülü sistemlerde gerçek zamanlı çalışmaya uygunluğu ve fundus görüntülerinden anlamlı derin özellikleri etkili şekilde çıkarabilme kapasitesidir. Ayrıca çalışmada, söz konusu önceden eğitilmiş modeller kullanılarak fundus görüntülerinden yüksek boyutlu derin özellik vektörleri elde edilmiştir. Bu özellikler daha sonra aşırı gradyan artırma (XGBoost), destek vektör makinesi (SVM), hafif gradyan artırma makinesi (LGBM), kategorik gradyan artırma (CatBoost) ve k-en yakın komşu (kNN) gibi farklı ML sınıflandırıcıları ile işlenmiş ve böylece hem DL hem de geleneksel ML yöntemlerinin güçlü yönlerini birleştiren kapsamlı bir hibrit sınıflandırma yapısı oluşturulmuştur. Performans değerlendirmesi için doğruluk, kesinlik, duyarlılık, F-skor ve eğri altında kalan alan (AUC) gibi temel sınıflandırma metrikleri kullanılmıştır. Deneysel bulgular, özellikle MobileNetv2+SVM hibrit modelinin dikkate değer bir üstünlük sergilediğini göstermektedir. Bu model, 0.9409 doğruluk, 0.9229 duyarlılık, 0.9221 F-skor ve 0.9229 AUC olmak üzere çalışma genelindeki en yüksek performans seviyelerini elde etmiştir. Bununla birlikte, en yüksek kesinlik değerinin (0.9264) MobileNetv3-small+LGBM modeli ile elde edilmiş olması, farklı MobileNet varyantlarının çeşitli sınıflandırıcılarla etkili şekilde bütünleştirildiğinde güçlü bir ayrım performansı sağlayabildiğini ortaya koymaktadır. Elde edilen sonuçlar, MobileNet tabanlı derin özellik çıkarımının glokom sınıflandırmasında yüksek ayırt edicilik sunduğunu ve önerilen hibrit yaklaşımın klinik karar destek sistemlerinde kullanılabilecek güvenilir, hızlı ve hesaplama açısından verimli bir çözüm olduğunu göstermektedir. Bu çalışma, özellikle düşük maliyetli ve gerçek zamanlı erken glokom tanı sistemlerinin geliştirilmesi için önemli bir temel oluşturmaktadır.
Göz Hastalıklarının Tespitinde Hafif Derin Öğrenme Mimarileri: Glokom Sınıflandırmasına Uygulanan MobileNet Varyantları
Keywords: Image and Video Coding; Resim ve Video Kodlama